Internalisasi Nilai-Nilai Agama pada Anak Usia Dini Melalui Redesain Masjid Besar Jatinom Klaten - Jannah, Rina Roudlotul; Jazariyah, Jazariyah (PROGRAM STUDI PENDIDIKAN GURU RAUDLATUL ATHFAL (PGRA) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2016)
This study aimed to reveal the importance of awareness about the redesign of the mosque as a center of education or powerful institution to internalize the values of religion in early childhood. The results showed that the mosque which is a container public education has a high impact for planting religious values in early childhood. Religious values should ideally be started since childhood. There are several stages of the process of internalization, namely First stage transformation of values is a step of delivering information about the redesign functions of mosques with child-friendly functions. The second stage of value transaction is a stage of dialogue in various directions in children with parent, tutor, mosques and community stakeholders. The third stage of the stages transinternalisasi applicative or their habit forming in worship at the mosque in early childhood.